Bone quality of laying hens fed different levels of fiber in the growth phase (7 to 17 weeks of age) - Cruz,Carlos Eduardo Braga (2012)
The effects of neutral detergent fiber levels (NDF) (145, 165, 185 g/kg) were assessed on the bone quality of light-weight and medium-weight laying hens. Eight hundred and forty laying hens were distributed in a completely randomized design in a 2 × 3 factorial arrangement (two strains and three NDF levels) with four replications of 35 birds. At the end of the growth phase, birds were transferred to a laying shed in the same experimental design and each experimental plot consisted of 14 birds. For bone assessment, two birds were selected per plot in the 17th week and one bird in the 35th week for slaughter. After slaughter, drumstick and thigh (legs) were removed and after deboning of the femur and tibia, taken to measurement of their length, weight, Seedor index, resistance, deformity, dry matter, mineral residue and crude protein. The data analysis showed no significant interaction between the factors NDF level and strain for any of the variables assessed at the different phases. The NDF level in the diet did not significantly influence bone growth, quality and composition at the end of the growing and laying phases. Medium-weight birds presented larger and heavier femur and tibia, with a greater Seedor index and less deformity, ash content and protein than the light-weight birds. Resistance did not vary significantly among the strains. A diet intended for laying hens at the growth phase can contain up to 185 g/kg NDF without causing problems in bone development and quality of laying hens.